The Development of Strategic Innovation in Mature Company Case Study: PT. Pryda Indonesia - Hermawan, Christine; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2012)
Growing opportunity in construction industry is no longer making PT. Pryda Indonesia experience growth. Revenue decline and the fading of company’s glory time put the company in mature stage that almost reach declining stage. The journal is made to find the root cause that make the revenue decline and recommend to arrange strategic innovation to solved PT. Pryda Indonesia’s problem. The framework to conduct strategic innovation is started with external analysis, internal analysis, and SWOT analysis to find the root cause of the problem. Unsuited STP become the root cause of the problem, because the company cannot compete with both lower price segments and high price segments and the company cannot also fulfill market needs and wants. Finaly, implementation plan is made to be started in January 2013. Keyword: Mature Company, PT. Pryda Indonesia, Strategic Innovation